1978
DOI: 10.1002/hlca.19780610743
|View full text |Cite
|
Sign up to set email alerts
|

Über Pterinchemie. 69 Mitteilung [1]. Konformationsanalyse von 5,6,7,8‐Tetrahydropteroinsäure und 5,6,7,8‐Tetrahydro‐L‐folsäure

Abstract: Conformational analysis of 5,6,7,8-tetrahydropteroic acid and 5,6,7,84etrahydro-~-foIic acid SummaryIn the 360-MHz-'H-NMR.-spectrum of (6 R, S)-9,9-dideuterio-5,6,7, S-tetrahydropteroic acid (racemic) (XIII) (AMX-System, Fig. 4) and (6R, S)-9,9-dideuterio-5,6,7,8-tetrahydro-L-folic acid (diastereomeric) (XVI) the Ha-C (6) and Ha-C(7) show a vicinal coupling constant of 6,7 Hz and the Ha-C(6) and He-C(7) one of 3,2 Hz. The first coupling constant provides evidence for an approximate trans-diaxal arrangement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The chemical shifts and spin-spin coupling constants observed in the spectrum replotted for Figure 2 for the major species of 5-CHO-H4folate are given in Table I. The assignments given in Table I are the same as those of tetrahydrofolate for the C(2/,6')-2H, C(3',5')-2H, -CH, t-CH2, /3-CHa, and /3-CHB resonances (Poe & Hoogsteen, 1978;Furrer et al, 1978).…”
Section: Resultsmentioning
confidence: 99%
“…The chemical shifts and spin-spin coupling constants observed in the spectrum replotted for Figure 2 for the major species of 5-CHO-H4folate are given in Table I. The assignments given in Table I are the same as those of tetrahydrofolate for the C(2/,6')-2H, C(3',5')-2H, -CH, t-CH2, /3-CHa, and /3-CHB resonances (Poe & Hoogsteen, 1978;Furrer et al, 1978).…”
Section: Resultsmentioning
confidence: 99%
“…NMR studies of CH2-H4folate by have shown that the resonances of the p-aminobenzoyl-L-glutamate moiety of CH2-H4folate exhibit about the same chemical shifts as corresponding protons of tetrahydrofolate (Poe & Hoogsteen, 1978;Furrer et al, 1978). Importantly, T atum et al (1977) demonstrated that the protons of the methylene bridge Cn were nonequivalent with a chemical shift difference of 1.21 ppm and geminal spin-spin coupling of 4 Hz.…”
Section: Results and Discussion Previousmentioning
confidence: 99%
“…A 13C NMR investigation (Armarego & Waring, 1980) and several 'H NMR studies (Storm & Chung, 1976;Weber & Viscontini, 1977; Armarego & Schou, 1977;Ganguly et al, 1981) of H4pterins and the closely related tetrahydrofolates (Poe & Benkovic, 1980;Poe et al, 1979a,b;Poe & Hoogsteen, 1978;Furrer et al, 1978) have concluded that the tetrahydropyrazine ring assumes one of two essentially equivalent cyclohexene-like half-chair conformations which differ only in the preferred orientations of their C6 and C7 substituents. Abbreviations: NMR, nuclear magnetic resonance; H4biopterin, 5,6,7,2-H4pterin, rranv-6,7-dimethyltetrahydropterin; cis-6,7-(CH3)2-H4pterin, m-6,7-dimethyltetrahydropterin; PAH, phenylalanine hydroxylase; TSP, 2,2,3,3tetradeuterio-3-(trimethyisilyl)propionate (sodium salt); D20, deuterium oxide; NADH, nicotinamide adenine dinucleotide (reduced form); d, deuterium (as used in naming the specifically deuterated analogues); DDQ, dichlorodicyanobenzoquinone; pH*, pH uncorrected for the deuterium isotope effect; FID, free induction decay; TCA, trichloroacetic acid; Hz, hertz; NOE, nuclear Overhauser effect.…”
mentioning
confidence: 99%